Modelling the regional variability of building activity in Greece: A multi-level multinomial logistic regression approach - Kantianis, Dimitrios; Polyzos, Serafeim; Tsiotas, Dimitrios (European Spatial Research and Policy, 2023)
This paper studies spatial differences in the fluctuations of the regional building activity in Greece, by developing a composite multinomial logistic regression model expressing the building activity’s variability in socio-economic terms. The results show that the variability in building activity is related to economies of scale within the construction sector, along with the performance of two other Greek economy’s major sectors, i.e., tourism and tertiary, in highlighting a dependence on the prime drivers of economic and regional development. Overall, the research provides empirical evidence on the macro-economic modelling of spatial demand, based on a proxy incorporating all aspects of human activity in the geographical space.